2(x+1)=3(x-4)+8

Simple and best practice solution for 2(x+1)=3(x-4)+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+1)=3(x-4)+8 equation:


Simplifying
2(x + 1) = 3(x + -4) + 8

Reorder the terms:
2(1 + x) = 3(x + -4) + 8
(1 * 2 + x * 2) = 3(x + -4) + 8
(2 + 2x) = 3(x + -4) + 8

Reorder the terms:
2 + 2x = 3(-4 + x) + 8
2 + 2x = (-4 * 3 + x * 3) + 8
2 + 2x = (-12 + 3x) + 8

Reorder the terms:
2 + 2x = -12 + 8 + 3x

Combine like terms: -12 + 8 = -4
2 + 2x = -4 + 3x

Solving
2 + 2x = -4 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
2 + 2x + -3x = -4 + 3x + -3x

Combine like terms: 2x + -3x = -1x
2 + -1x = -4 + 3x + -3x

Combine like terms: 3x + -3x = 0
2 + -1x = -4 + 0
2 + -1x = -4

Add '-2' to each side of the equation.
2 + -2 + -1x = -4 + -2

Combine like terms: 2 + -2 = 0
0 + -1x = -4 + -2
-1x = -4 + -2

Combine like terms: -4 + -2 = -6
-1x = -6

Divide each side by '-1'.
x = 6

Simplifying
x = 6

See similar equations:

| 18-2/3y=5/6y | | 7/6x+4=3x+2 | | 3p+3/3 | | 5.84-4.42x-1.2x=19.89 | | x+6y=9 | | 12x^2-4x=40 | | 1/4x-x=-15 | | 2x-2/3(3)=-16 | | 10(x-6)=2/5(x+4)-1/5x | | -4(x+2)-14=13+1 | | 7-3=m-8-4m | | 2*4*(29/4-(3*y))-2/3y=-16 | | 45x+45+47=25 | | 18/x=9/5 | | (18/x)*(5/9) | | 7(x-5)+23=9x-(2x+7)5 | | y+2=-3+6 | | x/4+3y=29/4 | | x+4/2=x-6/5 | | 2x-2/3y=-16 | | 52-6x=12x+20 | | 9x-4(-1)=22 | | 2(2.444444444+0.4444444444y)-y=5 | | x/2x-3=7/9 | | (-4/60)/(1/10) | | 18x=9+18x | | 2(x-7)-6=3(x-9) | | -4.25/.75= | | 4(x+4)/3=2x-2 | | -4/60/1/10 | | 9x-4y=22 | | -9.8+x+6.2=0 |

Equations solver categories